1991
DOI: 10.1104/pp.95.4.1265
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Net K+ Uptake Capacity of NaCl-Adapted Cells

Abstract: Maintenance of intracellular K+ concentrations that are not growth-limiting, in an environment of high Na+, is characteristic of NaCI-adapted cells of the glycophyte, tobacco (Nicotiana tabacum/gossii). These cells exhibited a substantially greater uptake of "Rb+ (i.e. an indicator of K+) relative to unadapted cells.Potassium uptake into NaCI-adapted cells was 1.5-fold greater than unadapted cells at 0 NaCI and 3.5-fold greater when cells were exposed to 160 millimolar NaCI. The difference in net K+ uptake bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 24 publications
(37 reference statements)
1
42
0
Order By: Relevance
“…Plants utilize two systems for K acquisition, low-and high-affinity uptake mechanisms. Low affinity of K uptake is not inhibited by Na but the high affinity process is restricted (Watad et al 1991). Similarly Na toxicity in plants is correlated with two proposed Na uptake pathways (Niu et al 1995).…”
Section: Effect Of Salinity On Mineral Accumulationmentioning
confidence: 94%
See 1 more Smart Citation
“…Plants utilize two systems for K acquisition, low-and high-affinity uptake mechanisms. Low affinity of K uptake is not inhibited by Na but the high affinity process is restricted (Watad et al 1991). Similarly Na toxicity in plants is correlated with two proposed Na uptake pathways (Niu et al 1995).…”
Section: Effect Of Salinity On Mineral Accumulationmentioning
confidence: 94%
“…An increase of K content in leaves in response to salinity evinces an enhanced transport of K from stem tissues to protect leaves. It is reported that uptake mechanisms of both K and Na are similar (Watad et al 1991). Plants utilize two systems for K acquisition, low-and high-affinity uptake mechanisms.…”
Section: Effect Of Salinity On Mineral Accumulationmentioning
confidence: 99%
“…The potassium target A large number of studies has shown the disruption of both cellular and whole-plant potassium homeostasis under sodium stress (Rains and Epstein 1967a, b, c;Flowers and Läuchli 1983;Watad et al 1991;Gaxiola et al 1992;Warne et al 1996;Zhu et al 1998 Takahashi et al 2007;Kronzucker et al 2008;Britto et al 2010;Coskun et al 2013, cf. Seemann andCritchley 1985).…”
Section: Sodium Toxicitymentioning
confidence: 99%
“…Sodium ions apparently nonsaline conditions but there is also evidence to compete with Ca^^ for uptake (Lynch, Cramer & indicate that it affects salinity tolerance under certain and/or affect intracellular levels of conditions (Lewis, Leidi & Lips, 1989), This could Ca^+ (Lynch & Lauchli, 1988;Lynch, Polito & be due to the fact that uptake and assimilation of Lauchli, 1989); Na+ also mcreases membrane NO3" and NH4+ have different energy requirements porosity (Van Steveninck, 1965, Watad et al, 1991 (Clarkson, 1986) and to interaction between NaCl and results in membrane depolarization (Lauchli, and nitrogen ion uptake. Since many natural and 1990), allowing the leakage of some ions and an agricultural lands which are saline are also N poor mflux of others.…”
mentioning
confidence: 99%